Financial Performance Analysis of Local Government in Managing the Regional Revenue and Expenditure Budget (APBD) in Bogor Regency - Annisa Alfiani; Diah Armeliza; Hafifah Nasution (PT. BATARI EDU CALYA, 2025)
This study aims to analyze the financial performance of the local government in managing the Regional Revenue and Expenditure Budget (APBD) of Bogor Regency, as well as to examine the supporting and inhibiting factors affecting such performance. The object of this research is the Bogor Regency Local Government. This study employs both secondary and primary data using a descriptive quantitative approach. The results indicate that the financial performance of the Bogor Regency Government during the period 2017–2022, measured using the decentralization degree ratio, falls into the “moderate” category, as it has not yet been able to fully finance governmental activities independently. The expenditure harmony ratio suggests that government spending has not been fully oriented toward capital or development expenditure. Furthermore, the regional dependency ratio remains very high, indicating strong reliance on central government transfers. However, the regional independence ratio is categorized as “moderate,” reflecting a gradual reduction in dependence on central government assistance. The effectiveness ratio of local own-source revenue (PAD) is optimal, demonstrating the government's ability to mobilize revenue in accordance with planned targets. The efficiency ratio indicates successful cost control in revenue collection, while both revenue and expenditure growth ratios show positive trends. Supporting factors for financial performance include improved employee competence, enhanced public service delivery, and better coordination with the central government, particularly regarding financial information systems and digital public services. Meanwhile, inhibiting factors include limitations in human resources, suboptimal financial administration systems, and the fact that PAD has not yet become the primary source of regional revenue.